Eksperimentasi Pendekatan Kontekstual Berbantuan Hands On Activity (HoA) Terhadap Kemampuan Pemecahan Masalah Matematik - Putra, Fredi Ganda (Universitas Islam Raden Intan Lampung, INDONESIA, 2017)
This research is comparative causal research with factorial design 3 × 1. The population of this research is all students of class VIII SMP Negeri 1 Simpang Semarang. Sampling was done by cluster random sampling. The sample of this research is students of class VIII B and VIII D. The instrument used to collect data is a test of mathematical problem solving ability of learners. Prior to use for data retrieval, the test instrument of mathematical problem solving ability was first tested. Assessment of validity of test instrument contents by 3 validators. Hypothesis test using one way Anova test with unequal cell. The conclusion of this research is that learners who get the application of contextual learning model with Hands on Activity has better problem solving ability than students who are given contextual learning model and conventional learning model, while the application of contextual learning model has better mathematical problem solving ability than the participants Students provided a contextual learning model and conventional learning model.